Overexpression of Cotton a DTX/MATE Gene Enhances Drought, Salt, and Cold Stress Tolerance in Transgenic Arabidopsis - Lu, Pu; Magwanga, Richard Odongo; Kirungu, Joy Nyangasi; Hu, Yangguang; Dong, Qi; Cai, Xiaoyan; Zhou, Zhongli; Wang, Xingxing; Zhang, Zhenmei; Hou, Yuqing; Wang, Kunbo; Liu, Fang (Frontiers in Plant Science, 2019)
Abiotic stresses have negative effects on plants growth and development. Plants, being sessile, have developed specific adaptive strategies that allow them to rapidly detect and respond to abiotic stress factors. The detoxification efflux carriers (DTX)/multidrug and toxic compound extrusion (MATE) transporters are of significance in the translocation of abscisic acid (ABA), a phytohormone with profound role in plants under various abiotic stress conditions. The ABA signaling cascades are the core regulators of abiotic stress responses in plants, triggering major changes in gene expression and adaptive physiological responses. We therefore carried out genome-wide analysis of the DTX/MATE gene family, transformed a DTX/MATE gene in Arabidopsis and carried out functional analysis under drought, salt and cold stress conditions. We identified 128, 70 and 72 DTX/MATE genes in Gossypium hirsutum, Gossypium arboreum and Gossypium raimondii, respectively. The proteins encoded by the DTX/MATE genes showed varied physiochemical properties but they all were hydrophobic. The Gh_D06G0281 (DTX/MATE) over-expressing Arabidopsis lines were highly tolerant under drought, salt and cold stress with high production of antioxidant enzymes and significantly reduced levels of oxidants. Lipid peroxidation, as measured by the level of malondialdehyde concentrations was relatively low in transgenic lines compared to wild types, an indication of reduced oxidative stress levels in the transgenic plants. Based on physiological measurements, the transgenic plants exhibited significantly higher relative leaf water content, reduced excised leaf water loss and a significant reduction in ion leakage as a measure of the cell membrane stability compared to the wild types. Abiotic stress responsive genes, ABF4, CBL1, SOS1 and RD29B were highly expressed in the transgenic lines compared to the non-transformed wild type plants. The protein encoded by the Gh_D06G0281 (DTX/MATE) gene was predicted to be located within the plasma membrane. Since signals from extracellular stimuli are transmitted through the plasma membrane most of which are conducted by plasma membrane proteins it is possible the Gh_D06G0281 (DTX/MATE) gene product could be important for this process.